Stakingsrecht [Voordrachten gehouden op het Landelijk Juridisch Studentencongres 1965 te Leiden] door J.M. van Bemmelen, H. Drion, P. Borst [e.a. Ten geleide van D.W.F. Verkade] (Kluwer, 1965)
Met bibliogr.